Analysis of the Green Building Concept in the Green Lake Viev Cimanggis Depok Apartment Building Based on Greenship EB 1.1 - Alvian Rahmad Saputra; M. Samer (Tinta Emas Publisher, 2023)
The growing human demand for space will continue to rise with the passage of time. Buildings serve as a tangible manifestation of this need for space. With increasing space requirements and development, the corresponding need for energy and its associated environmental impact is also on the rise. This necessitates in-depth studies related to Green Building practices. The primary objective of this research is to assess the environmental performance of buildings, with a specific focus on key aspects such as energy efficiency, water management, indoor air quality, and waste management. The research methodology involves conducting field surveys, gathering data through interviews with apartment management, scrutinizing relevant documentation, and conducting direct measurements related to energy and water consumption. The analysis of the Green Lake View Apartment in Cimanggis Depok reveals a Bronze category rating, amounting to 18 points, with a 37% achievement rate across several categories, including Land Use Appropriateness (ASD), Health and Comfort in Space (IHC), and Building Environment Management (BEM). To enhance the existing ratings, it is imperative to incorporate design recommendations to attain higher scores in future developments, aligning with the principles of sustainability within the construction industry. This research aspires to provide a comprehensive perspective on the practical application of Green Building concepts in apartment buildings. It further aims to offer valuable insights for the advancement and refinement of sustainable practices within the construction industry for the future.